2014
DOI: 10.1007/s12035-014-8951-y
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Partial Repair of Ribbon Synapse in Cochlear Inner Hair Cells After Ototoxic Withdrawal

Abstract: Ototoxicity is one of the major causes of sensorineural deafness. However, it remains unclear whether sensorineural deafness is reversible after ototoxic withdrawal. Here, we report that the ribbon synapses between the inner hair cells (IHCs) and spiral ganglion nerve (SGN) fibers can be restored after ototoxic trauma. This corresponds with hearing restoration after ototoxic withdrawal. In this study, adult mice were injected daily with a low dose of gentamicin for 14 consecutive days. Immunostaining for RIBEY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 55 publications
4
25
0
Order By: Relevance
“…Although partial recovery of auditory function after kanamycin treatment has been described previously, it only occured in regions with lower threshold shifts and greater OHC survival (82). The basis for this partial recovery is thought to be drug clearance from cochlear tissues, facilitating the repair of hair cell and strial physiology incurred during sub-lethal toxicity to resume optimal auditory function (25, 82, 84). However, once threshold shifts exceed >40 dB (akin to the LPS+kanamycin group), no functional or anatomical recovery of hair cells occurred, resulting in a PTS (82, 85).…”
Section: Discussionmentioning
confidence: 99%
“…Although partial recovery of auditory function after kanamycin treatment has been described previously, it only occured in regions with lower threshold shifts and greater OHC survival (82). The basis for this partial recovery is thought to be drug clearance from cochlear tissues, facilitating the repair of hair cell and strial physiology incurred during sub-lethal toxicity to resume optimal auditory function (25, 82, 84). However, once threshold shifts exceed >40 dB (akin to the LPS+kanamycin group), no functional or anatomical recovery of hair cells occurred, resulting in a PTS (82, 85).…”
Section: Discussionmentioning
confidence: 99%
“…Noise-induced synaptic loss is generally believed to be permanent; however, a few reports have suggested that synaptic loss may be partially reversible at early time points post-insult (Shi et al, 2013; Liu et al, 2015). Nonetheless, even in these models, synaptic counts are consistently reduced weeks after noise exposure, reinforcing the long-term irreversibility of synaptic loss without therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Liberman et al reported the reorganization of synaptic ribbon locations, the loss of synaptic ribbons, and the downregulation of AMPAR expression in the peripheral terminals after noise exposure [ 7 ]. Liu et al found that moderate ototoxicity in mice leads to reduced numbers and morphologic changes in the synaptic ribbons, which are accompanied by mild hearing loss but no significant loss of HCs or SGNs in the cochlea [ 8 ]. However, the mechanism behind these pathological changes in cochlear IHC ribbon synapse remains unclear.…”
Section: Introductionmentioning
confidence: 99%